التحليل الاقتصادي لمزارع أسماك المشط في وادي الأردن - الطراونة، محمد سالم; الطاهات، إبراهيم سليمان (جامعة الملك فيصل, 2018)
Fish meat is an important animal protein and nutrients that is needed for human body growth. This work aims to study the production costs of forty fish farms to determine the optimal size of production and optimum space and compare them with the actual size and space realized. Research results showed that feed accounted for 44.89 % of total costs while the ponds cost formed 3.71% of the total costs. The results also indicated that farmers do not achieve the optimal size of the production of 42.35 tons from the optimal farm size of 25.82 Donum (one Donum= 1000m2). Cost elasticity was 9.1 % with an average income of 63750 Jordanian Dinar (one Jordanian Dinar, JD= 1.41$) during a production season of seven months. The net profit reached 9800 JD, with a profit margin of 26610 JD. Revenues ratio of costs was 1.18. This indicates that every dinar invested in this project will yield 18 % of the Jordanian dinar. In light of these results, it is recommended to secure fodders at accepted prices to farmers as well as activating the role of agricultural extension in the field of fish farming.
تعد الأسماك من المصادر المهمة للبروتين والغنية بالعناصر الغذائية التي تلزم بناء ونمو جسم الإنسان. هدف البحث الحالي إلى دراسة تكاليف إنتاج 40 مزرعة من مزارع سمك المشط، وتحديد الحجم الأمثل للإنتاج، وتحديد المساحة المثلى ومقارنتها بالحجم والمساحة المتحققة فعلا. أوضحت نتائج البحث أن تكلفة الأعلاف شكلت 44.89% من إجمالي التكاليف الكلية، وبينت النتائج أن تكاليف إنشاء برك التربية شكلت 3.71 % من التكاليف الكلية، كما بينت النتائج أن المزارعين لا يحققون الحجم الأمثل للإنتاج البالغ 42.35 طن بمساحة مثلى قدرت ب 25.82 دونم (1 دونم =1000 متر مربع). بلغت مرونة التكاليف 9.1 % كما بلغ متوسط العائد 63750 دينارا أردنيا خلال فترة التربية التي امتدت سبعة أشهر، وبلغ الربح 9.8 آلاف دينار أردني، بهامش ربح 26610 دنانير أردنية، وبلغت نسبة العائدات إلى التكاليف 1.18، وهذا يشير إلى أن كل دينار مستثمر في هذا المشروع سوف يعطي 18% من الدينار. وفي ضوء نتائج الدراسة أوصى البحث بضرورة توفير الأعلاف بأسعار مقبولة من قبل المزارعين، وتفعيل دور الإرشاد الزراعي في مجال تربية الأسماك.
Keywords: الأسماك -- أسماك المشط -- مزارع الأسماك -- وادي الأردن